Outstanding library service to children : - Cerny, Rosanne (Association for Library Service to Children, American Library Association, 2006)
This book outlines and explains the "core competencies" necessary for librarians specializing in services for children. The Authors outline these seven competencies as being more than collection development and story hour. Each of the seven is explained in a separate chapter that includes a lengthy bibliography for further reading; for example, children's librarians must also know their clientele and acquire management skills